2019
DOI: 10.1186/s12882-019-1485-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial urinary tract infection among adult renal transplant recipients at St. Paul’s hospital millennium medical college, Addis Ababa, Ethiopia

Abstract: Background: Despite significant advances in surgical techniques, immunosuppression protocols, follow up periods and antimicrobial stewardship in modern medicine; post-renal transplantation urinary tract infection remained a major public health problem globally. This multiple serious squeals includes asymptomatic bacteriuria, cystitis and pyelonephritis. Among these, the bacterial origin of infection complications accounts for the most significant clinical, socioeconomic impacts in many countries of the world. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…demonstrated that 37% of bacteria considered as MDROs in kidney transplant recipients' UTIs [10]. Nevertheless, there are some studies showing higher rates of UTI with MDROs in kidney transplant recipients similar to our findings [19,20]. It is generally accepted that the prevalence of UTI caused by MDRO varies from country to country.…”
Section: Plos Onesupporting
confidence: 84%
“…demonstrated that 37% of bacteria considered as MDROs in kidney transplant recipients' UTIs [10]. Nevertheless, there are some studies showing higher rates of UTI with MDROs in kidney transplant recipients similar to our findings [19,20]. It is generally accepted that the prevalence of UTI caused by MDRO varies from country to country.…”
Section: Plos Onesupporting
confidence: 84%
“…17,18 Other bacterial species occurring were Klebsiella pneumoniae, coagulase-negative Staphylococci, group B Streptococcus, and Enterococci. 19,20 Gram-positive cocci have emerged as important causative agents of UTIs, particularly among elderly patients with predisposing conditions. 21 The inappropriate overuse of antimicrobial agents can lead to the development of antibiotic resistance, increased hospital cost, morbidity, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This finding represents the high prevalence of MDR uropathogens among renal transplantation recipients. In Kiros et al study, multidrug resistance was reported in 82% of the isolates among renal transplant recipients ( 30 ). In the study of Khosravi et al ( 31 ) , the most common resistance was reported against cefixime, cephalothin, and TMP/SMX, which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%